Magnesium isotopic variation in marine fish organs - Toshihiro Yoshimura; Naoto F. Ishikawa; Nanako O. Ogawa; Soichiro Kusaka; Shigeyuki Wakaki; Tsuyoshi Ishikawa; Kazuya Nagaishi; Masanori Kaneko; Yuta Isaji; Yoshito Chikaraishi; Naohiko Ohkouchi (Progress in Earth and Planetary Science)
Abstract Magnesium is a macro-nutrient for all living organisms, and its stable isotope ratios (δ26Mg) can be used for analyzing feeding habits and the dynamics of elements within the body. However, it was still unclear what kind of conditions for feeding and the surrounding seawater affect the Mg isotope ratios of marine fish. In this study, we report on the Mg isotopic composition of different organs of three fish species, blue mackerel (Scomber australasicus), black rockfish (Sebastes schlegeli), and Pacific bluefin tuna (Thunnus orientalis), as well as the magnitude of isotopic fractionation associated with Mg uptake in one-year-old T. orientalis. By using a delipidation treatment before acid samples digestion, the δ26Mg value of each organ was compared before and after removing the lipids and body fluids. In T. orientalis and S. schlegel, the δ26Mg of muscle and most internal organs is similar, whereas gills, fins, and bones are often 0.5‰ lower than the internal organs. We examined the variation in δ26Mg values for each organ using multiple T. orientalis individuals, and found that muscle tissue showed the least variable values among individuals. The δ26Mg of blood of one-year-old T. orientalis was clearly lower than the seawater value, and the value was close to that of its feed. This is thought to be the results that Mg2+ in seawater and blood plasma are separated each other in order to regulate osmotic pressure, and the contribution of Mg derived from feed is high. Isotopic fractionation of -0.40‰ was observed between the muscle of one-year-old T. orientalis and formula feed, similar to a cellular isotope fractionation between methanogen Methanothermobacter marburgensis and incubation medium. This is thought to reflect the selectivity of Mg uptake into the cell via membrane proteins.